1999
DOI: 10.1200/jco.1999.17.4.1141
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Hypersensitivity Reactions to Carboplatin

Abstract: Carboplatin hypersensitivity reactions develop in patients who have been extensively pretreated with the agent. The clinical features are highly variable, but they are sufficiently different from those noted after the administration of paclitaxel that it should not be difficult to distinguish between reactions to the two agents. As carboplatin is increasingly used as initial and second-line chemotherapy of ovarian cancer and other malignancies, it can be anticipated that hypersensitivity reactions to the drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
273
1
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(301 citation statements)
references
References 18 publications
20
273
1
7
Order By: Relevance
“…It is not surprising that after the introduction of platinum compounds into chemotherapy, their association with type I hypersensitivity reactions was confirmed (Cleare et al, 1976). These reactions were first described for CDDP with a 5 -20% incidence (Wiesenfeld et al, 1979;Shleback et al, 1995;Ö zgüroglu et al, 1999), and evidence regarding similar reactions for CBDCA are also available (Planner et al, 1991;Morgan et al, 1994;Weideman et al, 1994;Markman et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is not surprising that after the introduction of platinum compounds into chemotherapy, their association with type I hypersensitivity reactions was confirmed (Cleare et al, 1976). These reactions were first described for CDDP with a 5 -20% incidence (Wiesenfeld et al, 1979;Shleback et al, 1995;Ö zgüroglu et al, 1999), and evidence regarding similar reactions for CBDCA are also available (Planner et al, 1991;Morgan et al, 1994;Weideman et al, 1994;Markman et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…For other platinum compounds, this kind of reaction is well known (Cleare et al, 1976;Wiesenfeld et al, 1979;Planner et al, 1991;Morgan et al, 1994;Weideman et al, 1994;Shleback et al, 1995;Markman et al, 1999;Ö zgüroglu et al, 1999). On data sheets of OHP, these clinical features are not stressed.…”
mentioning
confidence: 99%
“…Although five patients stopped because of cumulative toxicity, three of these were from the previously well-described allergic reactions to carboplatin occurring after many courses. 33 Consistent with the American Society of Clinical Oncology treatment guidelines, at the time this study opened it was not the standard practice to treat beyond six or eight courses with frontline platinum doublets at UT M. D. Anderson Cancer Center. More recent recommendations are that patients without response should be treated with four cycles and no more than six cycles in patients with response.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study at the Cleveland Clinic Cancer Center [22] reported that hypersensitivity to carboplatin developed in 12% of carboplatin-treated patients. Because of the possibility of fatal cross-hypersensitivity, the use of cisplatin in patients who have developed hypersensitivity to carboplatin is not recommended [23].…”
Section: Platinum Agentsmentioning
confidence: 99%